ANÁLISE DO DESEMPENHO TERMOACÚSTICO DE TIJOLOS DE ADOBE COM ADIÇÃO DE POLIESTIRENO EXPANDIDO - Santos, Luana; Prado, Andreia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In order to present alternatives that minimize the environmental impacts of construction, from the use of recycled and/or reused raw materials, in contrast to the large volumes of extraction of natural resources in the sector, this work produced and evaluated, mechanically, pure adobes and with different contents of expanded polystyrene (EPS), for further diagnosis of their thermoacoustic performance in masonry systems of fence, according to the norms of the Brazilian Association of Technical Standards (ABNT), mainly in Brazilian Regulatory Norm (NBR) 15575 of 2013. The mechanical characterization allowed the choice of an addition content that, like the pure bricks, was used in a building prototype, to evaluate the performance by means of measurements. The analysis of the thermal insulation comprised the realization of calculations that, using linear relations, revealed the minimum performance to the two types of prototypes, and of measurements that suggested the attendance at the "intermediate" level of performance. The acoustic insulation analysis, on the other hand, showed, in a general way, sound pressure levels higher than the limits of comfort, presenting characteristics acceptable in only two moments, at night.